2013
DOI: 10.1021/ac402379y
|View full text |Cite|
|
Sign up to set email alerts
|

Structural Characterization of Gangliosides and Glycolipids via Ultraviolet Photodissociation Mass Spectrometry

Abstract: Ultraviolet photodissociation (UVPD) mass spectrometry was used to characterize the structures of amphiphilic glycosphingolipids and gangliosides in comparison to collision induced dissociation (CID) and higher energy collision dissociation (HCD) in a high performance Orbitrap mass spectrometer. UVPD produced the widest array of fragment ions diagnostic for both the ceramide base and oligosaccharide moieties. CID and HCD generated mainly glycosidic B/Y and C/Z cleavages of the oligosaccharides moieties and ver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
70
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 59 publications
(80 citation statements)
references
References 65 publications
(117 reference statements)
3
70
1
Order By: Relevance
“…Other ganglioside lipid classes, including GM1, GM2, GD2, GT2, and GP, were not observed in this study above the limits of detection using either retina tissue extraction method. In order to confi rm the putative retina ganglioside species identifi ed by accurate mass measurements, negative ionization mode HCD-MS/MS was utilized to detect the presence of characteristic ganglioside product ions in both the modifi ed Svennerholm upper phase and monophasic retina lipid extracts, as previously described ( 56 ), and by comparison to HCD-MS/MS results obtained from commercially available ganglioside standards. As shown in Fig.…”
Section: Evaluation Of Retina Ganglioside Profi Les From Monophasic Vmentioning
confidence: 99%
“…Other ganglioside lipid classes, including GM1, GM2, GD2, GT2, and GP, were not observed in this study above the limits of detection using either retina tissue extraction method. In order to confi rm the putative retina ganglioside species identifi ed by accurate mass measurements, negative ionization mode HCD-MS/MS was utilized to detect the presence of characteristic ganglioside product ions in both the modifi ed Svennerholm upper phase and monophasic retina lipid extracts, as previously described ( 56 ), and by comparison to HCD-MS/MS results obtained from commercially available ganglioside standards. As shown in Fig.…”
Section: Evaluation Of Retina Ganglioside Profi Les From Monophasic Vmentioning
confidence: 99%
“…44,46 We have explored UVPD at 193 nm for characterization of glycolipids, including lipid A, and found that UV photoexcitation promotes extensive C-C, C-N, C-O, glycosidic and cross-ring cleavages which contribute to the highly informative fragmentation patterns observed upon UVPD. 41,6166 UVPD has allowed unusual modifications to be accurately pinpointed and isobaric species to be differentiated. 41,6166 …”
Section: Introductionmentioning
confidence: 99%
“…Also, in order to identify structural isomers cleavage of "inert" C-C and C-N bonds in the lipid part are highly desirable. A novel MS/MS fragmentation technique, UVPD (ultraviolet photodissociation) excels in both these aspects [55,[57][58][59].…”
Section: Ms Analysis Of Lipidsmentioning
confidence: 99%
“…Phospholipids and glycolipids represent a diverse class of lipids, and have been studied the most amongst lipids using various MS techniques over the last decade [3,4,[55][56][57][58][59]. MALDI MS/MS approach, using diagnostic precursor ion and neutral loss scans was shown to be highly efficient for analysis of biological lipid mixtures [3].…”
Section: Ms Analysis Of Lipidsmentioning
confidence: 99%
See 1 more Smart Citation